Multifunctional composite with hybrid carbon fiber and carbonaceous coconut particle reinforcement - Feni, Foster; Jahan, Maryam; Zhao, Rong; Li, Guoqiang; Zhao, Guang-Lin; Mensah, Patrick F. (Frontiers in Materials, 2023)
The utilization of multifunctional composite materials presents significant advantages in terms of system efficiency, cost-effectiveness, and miniaturization, making them highly valuable for a wide range of industrial applications. One approach to harness the multifunctionality of carbon fiber reinforced polymer (CFRP) is to integrate it with a secondary material to form a hybrid composite. In our previous research, we explored the use of carbonaceous material derived from coconut shells as a sustainable alternative to inorganic fillers, aiming to enhance the out-of-plane mechanical performance of CFRP. In this study, our focus is to investigate the influence of carbonized coconut shell particles on the non-structural properties of CFRP, specifically electromagnetic interference (EMI) shielding, thermal stability, and water absorption resistance. The carbonized material was prepared by thermal processing at 400 °C. Varying proportions of carbonized material, ranging from 1 to 5% by weight, were thoroughly mixed with epoxy resin to form the matrix used for impregnating woven carbon fabric with a volume fraction of 29%. Through measurements of scattering parameters, we found that the hybrid composites with particle loadings up to 3% exhibited EMI shielding effectiveness suitable for industrial applications. Also, incorporating low concentrations of carbonized particle to CFRP enhances the thermal stability of hybrid CFRP composites. However, the inclusion of carbonized particle to CFRP has a complex effect on the glass transition temperature. Even so, the hybrid composite with 2 % particle loading exhibits the highest glass transition temperature and lowest damping factor among the tested variations. Furthermore, when subjected to a seven-day water immersion test, hybrid composites with 3% or less amount of carbonized particle showed the least water absorption. The favorable outcome can be attributed to good interfacial bonding at the matrix/fiber interface. Conversely, at higher particle concentrations, aggregation of particles and formation of interfacial and internal pores was observed, ultimately resulting in deteriorated measured properties. The improved non-structural functionalities observed in these biocomposites suggest the potential for a more sustainable and cost-effective alternative to their inorganic-based counterparts. This advancement in multifunctional composites could pave the way for enhanced applications of biocomposites in various industries.